Has-miR-199a-3p/RELA/SCD inhibits immune checkpoints in AMD and promotes macrophage-mediated inflammation and pathological angiogenesis through lipid metabolism pathway: A computational analysis. - Jiang Jiang; Shu Wang; Yun Li; Yi Wang; Rongfeng Liao (PLoS ONE, 2024)
More and more evidence shows that abnormal lipid metabolism leads to immune system dysfunction in AMD and promotes the occurrence of AMD by changing the homeostasis of ocular inflammation. However, the molecular mechanism underlying the effect of lipid metabolism on the phenotype and function of macrophages is still unclear, and the mechanism of association between AMD and cancer and COVID-19 has not been reported. The purpose of this study is to explore the interaction between lipid metabolism related genes, ferroptosis related genes and immunity in AMD, find out the key genes that affect the ferroptosis of AMD through lipid metabolism pathway and the molecular mechanism that mediates the action of macrophages, and find out the possible mechanism of lipid metabolism and potential co-therapeutic targets between AMD and cancer and COVID-19, so as to improve treatment decision-making and clinical results. For the first time, we have comprehensively analyzed the fatty acid molecule related genes, ferroptosis related genes and immune microenvironment of AMD patients, and determined that mast cells and M1 macrophages are the main causes of AMD inflammation, and found that SCD is the core gene in AMD that inhibits ferroptosis through lipid metabolism pathway, and verified the difference in the expression of SCD in AMD in a separate external data set. Based on the analysis of the mechanism of action of the SCD gene, we found for the first time that Has-miR-199a-3p/RELA/SCD is the core axis of action of lipid metabolism pathway to inhibit the ferroptosis of AMD. By inhibiting the immune checkpoint, we can enhance the immune cell activity of AMD and lead to the transformation of macrophages from M2 to M1, thereby promoting the inflammation and pathological angiogenesis of AMD. At the same time, we found that ACOX2 and PECR, as genes for fatty acid metabolism, may regulate the expression of SCD during the occurrence and development of COVID-19, thus affecting the occurrence and development of AMD. We found that FASD1 may be a key gene for the joint action of AMD and COVID-19, and SCD regulates the immune infiltration of macrophages in glioma and germ line tumors. In conclusion, our results can provide theoretical basis for the pathogenesis of AMD, help guide the treatment of AMD patients and their potentially related diseases and help to design effective drug targets.